2023
DOI: 10.1149/2162-8777/acce05
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diethanolamine on Chemical Mechanical Polishing in Alkaline Glycine-Based Slurries for Cobalt Interconnects

Abstract: Cobalt (Co) and its low resistivity, superior adhesion property, and void-free seamless fill ability, pledge to transform the landscape of integrated circuits in many areas, especially in interconnects and logic contacts. Chemical mechanical polishing (CMP), which can realize local and global planarization, has been recognized as one of the indispensable manufacturing approaches for the fabrication of multilevel metal interconnection structures. The present work introduces diethanolamine (DEA) into our alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Typically, the manufacturing process of Co contact plugs and interconnects comprises etching trenches into dielectric layers, depositing diffusion barrier layers (titanium/titanium nitride, Ti/TiN) and wiring metals (Co) from bottom to top, followed by the removal of overburden materials utilizing chemical mechanical polishing (CMP), which is the most effective technique to realize the local and global planarization of wafer surfaces . One of the most common slurries for Co is composed of colloidal silica (SiO 2 ) as abrasive particles, accompanied by an oxidizer, a complexing agent, a corrosion inhibitor, plus one or more of a long list of additives. Inevitably, the Co surfaces after the CMP process have to contend with a significant number of defects that include remaining SiO 2 particles, polishing debris, organic residues, severe corrosion, and scratches, which both can easily produce pores and holes in the following lithography and ion implantation steps, leading to short circuits . As a result, there is a need for the indispensable post-CMP cleaning process prior to any further step to minimize these contaminations and then ensure high yield and quality of circuits …”
Section: Introductionmentioning
confidence: 99%
“…Typically, the manufacturing process of Co contact plugs and interconnects comprises etching trenches into dielectric layers, depositing diffusion barrier layers (titanium/titanium nitride, Ti/TiN) and wiring metals (Co) from bottom to top, followed by the removal of overburden materials utilizing chemical mechanical polishing (CMP), which is the most effective technique to realize the local and global planarization of wafer surfaces . One of the most common slurries for Co is composed of colloidal silica (SiO 2 ) as abrasive particles, accompanied by an oxidizer, a complexing agent, a corrosion inhibitor, plus one or more of a long list of additives. Inevitably, the Co surfaces after the CMP process have to contend with a significant number of defects that include remaining SiO 2 particles, polishing debris, organic residues, severe corrosion, and scratches, which both can easily produce pores and holes in the following lithography and ion implantation steps, leading to short circuits . As a result, there is a need for the indispensable post-CMP cleaning process prior to any further step to minimize these contaminations and then ensure high yield and quality of circuits …”
Section: Introductionmentioning
confidence: 99%
“…Based on the above research results, it was found that compared to inorganic bases, mixing organic alkalis with inorganic bases as regulators can greatly improve the stability of slurry, and also have a significant impact on polishing efficiency and surface quality after polishing. L. Zhang et al 26 investigated at low concentrations, that diethanolamine (DEA) could be able to accelerate the polishing process via its auxiliary complexing effect, obtaining higher removal rates. X. Lin et al 27 found that 2-amino-2-methyl-1-propanol (AMP) not only has the function of regulating and stabilizing pH values but also has the function of dispersing abrasives and surfactants.…”
mentioning
confidence: 99%